The Effect of Experiential Brand Activation Through Vidio's "Roaring Night" Event on Customer Trust - Faaiz, Muhammad Al; Dianita, Indria Angga; Gracia, Amanda Bunga; Seprina, Wa Ode (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2024)
The growth of Over-The-Top (OTT) services has led to a cultural shift towards streaming, which has been accompanied by a rise in content piracy. As the official broadcaster for the English Premier League in Indonesia, Vidio encounters significant challenges from piracy that undermine customer trust and loyalty. Declines in customer trust can lead to increased customer attrition and reduced loyalty. To address these issues and rebuild customer trust, Vidio implemented an Experiential Brand Activation strategy through the "Roaring Night" event. This study investigates how Experiential Brand Activation affects customer trust using a quantitative research method, surveying 400 members from 11 English Premier League fan communities in Jakarta. The findings show a positive link between Experiential Brand Activation and customer trust. However, the correlation analysis reveals a weak but statistically significant relationship (coefficient 0.180, p = 0.000), with Experiential Brand Activation accounting for only 3.2% of the variance in customer trust. This indicates that other factors also play a role. Future research should use qualitative methods to explore these additional factors, including customer engagement, celebrity endorsements, and loyalty. This study provides valuable insights for OTT marketing strategies, highlighting the importance of a holistic approach to enhancing long-term consumer trust and loyalty. Studi ini memberikan wawasan berharga untuk strategi pemasaran OTT, menyoroti pentingnya pendekatan holistik untuk meningkatkan kepercayaan dan loyalitas konsumen jangka panjang.